Imitation versus innovation: What makes the difference? - Spyros Arvanitis; Florian Seliger (ETH Zurich, KOF Swiss Economic Institute, 2014)
The main objective of this empirical paper is to identify characteristics of imitation and innovation and shed light on possible differences between these two kinds of innovative activity. Thus, it tries to answer the following questions: (a) what are the determinants of imitative performance compared to determinants of innovative performance and (b) what are the determinants of switching from imitative to innovative behavior compared to imitators and innovators showing persistence over time. The study is based on Swiss firm data. In sum, our findings indicate that imitating firms are significantly more 'extroverted' than innovating firms because their activities are much more related to external R&D activities and cooperation and medium-educated personnel. Innovating firms do not rely to the same extent on the exploration of external knowledge. Their rather 'introverted' behavior seems be more related with intense exploitation of internal resources. Further, the profiles of different types of innovating firms show that an innovation performance hierarchy exists ranking from occasional innovators through switchers to persistently innovating firms.
Keywords: O31; 330; innovation; imitation